2006
DOI: 10.3758/bf03213931
|View full text |Cite
|
Sign up to set email alerts
|

Attention alters the appearance of motion coherence

Abstract: Selective attention enhances visual information processing, as measured by behavioral performance and neural activity. However, little is known about its effects on subjective experience. Here, we investigated the effect of transient (exogenous) attention on the appearance of visual motion, using a psychophysical procedure that directly measures appearance and controls for response bias. Observers viewed pairs of moving dot patterns and reported the motion direction of the more coherent pattern. Directing atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 41 publications
4
81
0
Order By: Relevance
“…Thus, a long interval between the cue and target should eliminate any effect that it may have on perception, and any residual difference between the neutral and peripheral cues would be attributed to a cue bias. When the cue preceded the display by 500 msec, there were no systematic differences between the neutral and peripheral conditions in the appearance of contrast (Carrasco, Ling, & Read, 2004) and of motion coherence (Liu et al, 2006). Thus, when transient attention was no longer active, the appearance of the stimulus was not altered.…”
Section: Cue Biasmentioning
confidence: 85%
See 3 more Smart Citations
“…Thus, a long interval between the cue and target should eliminate any effect that it may have on perception, and any residual difference between the neutral and peripheral cues would be attributed to a cue bias. When the cue preceded the display by 500 msec, there were no systematic differences between the neutral and peripheral conditions in the appearance of contrast (Carrasco, Ling, & Read, 2004) and of motion coherence (Liu et al, 2006). Thus, when transient attention was no longer active, the appearance of the stimulus was not altered.…”
Section: Cue Biasmentioning
confidence: 85%
“…Whereas in many studies investigating the effect of attention on performance in visual tasks a black peripheral cue has been used (Carrasco, Ling, & Read, 2004;Carrasco et al, 2000;Hsieh et al, 2006;Lu & Dosher, 1998, a green cue has shown to affect texture segmentation (Yeshurun & Carrasco, 1998 and to improve acuity (Yeshurun & Carrasco, 1999). Using a black cue, as in the apparent-contrast article referred to (Carrasco, Ling, & Read, 2004), transient attention has been shown to increase perceived spatial frequency and gap size (Gobell & Carrasco, 2005), as well as perceived motion coherence (Liu et al, 2006) and perceived speed (Turatto et al, 2007). Using a white precue, we have also reported that transient attention increases perceived flicker (Montagna & Carrasco, 2006) and perceived color saturation, but not hue .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such cueing effects are typically interpreted as attention effects: It is assumed that spatial attention facilitates the perception of stimuli presented at the cued location. While some studies focused on response speed (Posner, 1980;Posner, Snyder & Davidson, 1980;Jonides, 1981), other studies used perceptual decision tasks to test response accuracy (Bashinski & Bacharach, 1980;Dosher & Lu, 2000;Carrasco, Ling & Read, 2004;Liu, Fuller & Carrasco, 2006;Fairhall & Macaluso, 2009).…”
Section: Introductionmentioning
confidence: 99%